Effects of harbor activities on sediment quality in a semi-arid region in Brazil - Moreira, Lucas B. [UNESP]; Castro, Ítalo B.; Hortellani, Marcos A.; Sasaki, Silvio T.; Taniguchi, Satie; Petti, Mônica A.V.; Fillmann, Gilberto; Sarkis, Jorge E.S.; Bícego, Márcia C.; Costa-Lotufo, Leticia V.; Abessa, Denis M.S. [UNESP] (Elsevier, 2017)
Tropical marine environments are rich in biodiversity and the presence of harbor activities in these areas can harm the coastal ecosystems. In this study, we assessed sediment quality of two harbors from a tropical region in Brazil by applying multiple lines-of-evidence approach. This approach included the integration of results on: (1) grain size, organic matter, organic carbon, nitrogen, phosphorus, trace metals, polycyclic aromatic hydrocarbons, linear alkylbenzenes, and tributyltin; (2) acute toxicity of whole sediments and chronic toxicity of liquid phases; and (3) benthic community descriptors. Our results revealed that the main contaminants detected in sediments from Mucuripe and Pecém Harbors were chromium, copper, nitrogen, zinc, and tributyltin. These toxicants arise from typical harbor activities. However, the changes in benthic composition and structure appear to depend on a combination of physical impacts, such as the deposition of fine sediments and the toxic potential of contaminants, especially in Mucuripe. Thus, apart from toxicants physical processes are important in describing risks. This information may assist in management and conservation of marine coastal areas.
Keywords: Dredging; Environmental management; Marine pollution; Sediment quality triad; Sediment toxicity; Tropical environments